Análisis de los consumos históricos de agua potable del cantón Catamayo - Sarango Guayllas, Fernando Atahualpa (2023)
ABSTRAC The deficit in water coverage in the populations of Ecuador results from various factors, among the main ones are: socioeconomic, sociodemographic, climatological, management and water quality factors. In turn, the use of an outdated standard in the designs of drinking water systems would aggravate the situation. For this reason, this research aims to analyze the historical consumption of drinking water in the Catamayo canton of the province of Loja. The data obtained regarding the monthly consumption of drinking water per user in the residential area of the canton by the municipal department of drinking water and sewage of the Catamayo canton corresponds to a period from January 2010 to May 2022. The data was manually purified. primary using the Excel program to eliminate anomalous values and with the Minitab software to remove atypical data, through a statistical analysis it is established that the maximum historical consumption in the Catamayo canton was 30,175 m3 recorded in June 2020, the historical minimum consumption was In May of the same year, it reached 11,649 m3 and the historical average was 18,444 m3. With the results obtained in the statistical analysis, the coefficient of variation of maximum daily consumption for the Catamayo canton was determined (Kd =1.64). This value, when compared with the range of the kd established by the Ecuadorian standard CPE INEN 005-9-1 (1.3 – 1.5), shows that the Kd found for the canton is above the range of the Standard, which shows the existence of a deficit in water coverage. This result will be able to generate efficient drinking water systems for the Catamayo canton. Keywords: Drinking water, coefficient of variation